6th ICBSTA - Book of abstracts - Faculty of science, Omar Al- Mukhtar University (AlQalam Journal of Medical and Applied Sciences, 2024)
Sixth International Conference of Basic Sciences and Their Applications (6th ICBSTA) is an event hosted by Elbeida City in Faculty of science - Omar AlMukhtar University. This conference aims to exchange scientific experiences and suggestions to solve various problems facing our country in the fields of basic sciences, The conference is an excellent opportunity to learn about the latest scientific research in various basic sciences and applications. المؤتمر الدولي السادس للعلوم الأساسية وتطبيقاتها هو حدث علمي مميز تستضيفه مدينة البيضاء في رحاب كلية العلوم بجامعة عمر المختار. ويهدف هذا المؤتمر لتبادل الخبرات العلمية واقتراح الحلول الممكنة لمختلف المشاكل التي تواجه بلادنا في مجالات العلوم الأساسية. ويعتبر المؤتمر فرصة ممتازة للإطلاع على أخر الأبحاث العلمية في مختلف العلوم الأساسية وتطبيقاتها السابقة